The usability of Burger body model on determination of oriented strand boards’ creep behavior - Nadir Yildirim; Stephen Shaler; William West; Ema Gajic; Russel Edgar (Advanced Composites Letters, 2020)
In this work, the usability of the Burger body model (BBM) for determining the behavior of oriented strand boards (OSBs) under long-term loads was evaluated. The actual bending strain data and predicted strain data as a function of different stress levels and load durations under constant environmental conditions (25 ± 2°C and 50% relative humidity) were compared. Two test groups, short-term bending tests and long-term creep-rupture bending tests, were performed according to relevant ASTM standards. Specimens were randomly assigned to three groups and loaded at 47% (132.2 kg), 51% (137.4 kg), or 55% (154.9 kg) of the mean static short-term flexural strength. Specimen creep was monitored for 10,000 h using an automated measurement system. The four-parameter BBM parameters were obtained for all specimens at 2000-h time intervals, providing five different estimates. Measured strain values were compared with strain predictions from the BBM and with the goal of evaluating length of experiment on prediction accuracy. Each stress level provided statistical differences based on the error between the actual strain and predicted strain values. Group 3 provided minimum error compared to group 1 and group 2. The 10,000 and 8000 h loading provided the most accurate predictions compared to 6000, 4000, and 2000 h of data. Overall, the longer the actual data is collected the more accurate predictions were obtained. As a result, the BBM was found useful tool for predicting the creep behavior of OSBs under different loads and load durations. It was also shown that the increased duration of practical loading minimizes the error between the prediction. Therefore, the BBM is suggested for use predicting the creep behavior of OSBs over 8000 h load durations.